PERANAN SUKARNO RAJITA SEBAGAI TOKOH PEJUANG OPERASI TRIKORA DI IRIAN BARAT TAHUN 1961-1962 - Herdin, Yulia; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Sukarno Rajita was one of the military figures of the Indonesian army of the armed forces that operation trikora in West Irian in 1961-1962. Sukarno Rajita was born in Cirebon, October 2, 1939 by parents named Rajita and Ratiah. Sukarno Rajita was the first child of seven siblings and played a role in operation trikora in West Irian. The purpose of this study was to determine the background of the life of Sukarno Rajita, to figure out the role of Sukarno Rajita as a figure in the operation of operation trikora in West Irian, to determine the values of the struggle of Sukarno Rajita as to figure out the operation of trikora operation in West Irian and to determine the performance of Sukarno Rajita from the government. Data analysis uses historical writing method that consists of different phases, namely heuristics, criticis, interpretation and historiography. The results of this study were that Sukarno Rajita followed special military training for gun commanders. Sukarno Rajita carried out the operation of trichora in 1961 in the context of the liberation of Western Irish. He was assigned as Tamtama to measure distances to measure the range of fire of an air rifle. During the operation of the trichora, Sukarno Rajita used the main weapon system (defense equipment) with the use of air defense, the cannon. After completing the operations, Sukarno Rajita was placed in the Pekanbaru area. When he retired, Sukarno Rajita joined the Indonesian Veterans Legion Organization.Key Words: Sukarno Rajita, Operation Trikora in West Irian, Role.